Genetics and cell biology of vancomycin resistance in clostridioides difficile - Henriques, Bruna (2024)
Abstract: Clostridioides difficile infections (CDI) significantly affect thousands of individuals globally and impose a substantial burden on healthcare facilities. The standard treatment for CDI is Vancomycin (VAN), whose lethal target is the D-alanyl-D-alanine (D-Ala-D-Ala) motif in lipid II, which inhibits proper peptidoglycan (PG) polymerization. Some pathogens harbour van clusters that confer resistance to VAN by producing lipid II with a D-alanyl-D-serine (D-Ala-D-Ser) motif, with reduced VAN binding affinity. C. difficile possesses a vanG-type cluster, which is induced in the presence of VAN but does not raise the minimum inhibitory concentration (MIC) significantly (MIC < 2 mg/L). While other pathogens with vanG clusters exhibit significantly higher MICs (16 mg/L), no epidemic C. difficile strains with comparable resistance have been described. We hypothesize that C. difficile has intrinsic limiting factors (bottlenecks) that prevent expression of higher resistance levels. Here, we reveal three frequently mutated genes in our VAN-resistant (VANR ) isolates: sdaB, murG and vanS. Deletion of sdaB, which codes for a L-serine deaminase that produces pyruvate from L-serine, had been previously shown to result in elevated VAN resistance (MIC 4 mg/L). A mutation in murG, essential for lipid II synthesis, had also been linked to increased resistance (MIC 16 mg/L). Additionally, mutations in vanS, which encodes the sensor kinase required for transcription of the vanG cluster, resulted in increased expression of the cluster in VANR isolates. Altogether, these mutations suggest that the intracellular pool of serine, the level of expression of the vanG cluster and murG activity towards D-Ala-D-Ser substrates may be bottlenecks that prevent VAN resistance. To assess the roles of the vanS, sdaB and murG in VAN resistance, we first deleted the vanRS operon in an otherwise WT background and in a sdaB deletion mutant. Using VAN gradient plates we found that the deletion of vanRS is epistatic over sdaB indicating that the VanRS system is required for the increased resistance to VAN caused by the sdaB mutation and hence that the two vanRS and sdaB genes function in the same pathway. We also found that: i) vanS alleles coding for constitutively active forms of VanS do not result in increased resistance to VAN per se, or in the presence of the sdaB mutation; ii) the murG alleles did not increase resistance to VAN in an otherwise WT background. Since the increased resistance caused by sdaB requires VanRS but increased activity of VanRS does not confer increased resistance to VAN, even in the presence of a sdaB deletion, a third bottleneck may exist. This third bottleneck may involve the level of expression and/or activity of MurG but this remains to be tested. In all, our results highlight the role of serine availability in conjunction with the vanRS system in VAN resistance. Our results also reinforce the view that VAN resistance rises by different pathways in C. difficile.